Application of Dispersive Liquid–Liquid Microextraction Followed by High‐Performance Liquid Chromatography/Tandem Mass Spectrometry Analysis to Determine Tetrabromobisphenol A in Complex Matrices. (16th September 2020) - Macêdo, Williane Vieira; Bernegossi, Aline Christine; Sabatini, Carolina Aparecida; Corbi, Juliano José; Zaiat, Marcelo
Abstract: An accurate and sensitive ultrasound‐dispersive liquid–liquid microextraction technique followed by high‐performance liquid chromatography separation coupled with electrospray ionization tandem mass spectrometry detection method to determine the presence of tetrabromobisphenol A (TBBPA) in complex environmental matrices is proposed. The miniaturized procedure was used to extract and quantify the analyte in domestic sewage, anaerobic sludge, and the aquatic test organism species Daphnia magna and Chironomus sancticaroli, which are standardized organisms for ecotoxicity bioassays. Limits of detection of 2 ng L −1 (domestic sewage), 2 ng g −1 (anaerobic sludge), 0.25 ng g −1 ( D. magna ), and 5 ng g −1 ( C. tentans ) were obtained. The presence of TBBPA was determined in domestic sewage and anaerobic sludge from an anaerobic batch bioreactor at a concentration of 0.2 ± 0.03 μg L −1 and 507 ± 79 ng g −1, respectively. In D. magna and C. sancticaroli exposed to TBBPA in an acute toxicity bioassay, the micropollutant accumulated at 3.74 and 8.87 μg g −1, respectively. The proposed method is a simple and cost‐effective tool to determine TBBPA environmental occurrence and biomagnification potential compared with conventional extraction methods. To the best of our knowledge, this is the first liquid–liquid miniaturized extraction method to be applied to D. magna and C. sancticaroli. Environ Toxicol Chem 2020;39:2147–2157. © 2020 SETAC Abstract : TBBPA quantification in complex matrices. DLLME‐HPLC‐ESI‐MS/MS = dispersive liquid–liquid microextraction‐high‐performance liquid chromatography‐ionization–tandem mass spectrometry.